KREATIVITAS DALAM PEMBELAJARAN LITERASI TEKS SASTRA - R. Mekar Ismayani (STKIP Siliwangi, 2013)
The middle warm terms discussed in education related to the change of curriculum KTSP (2006) into the curriculum in 2013 that the scientific approach, text-based learning, and Indonesian as the tractor all subject. However, when examined more deeply, especially for Indonesian subjects, is more focused on aspects of creativity and literacy skills of students. Creativity and literacy skills into a foundation thatshould be owned by everyone, because both can lead a nation towards progress. In other words, a person's creativity and literacy skills can be used as a parameter to measure the quality of education that will ultimately determine the quality of human resources. Someone literacy skills, one of which will appear on the ability to read and write. Reading and writing is an activity that involves creativity, because both the language skills of a creative activity. Reading and writing are like two sides of a coin can not be separated each other and influence each other. Therefore, reading and writing should be provided in an integrated. This paper will raise about creativity in teaching literacy literary texts. Why literature? Because in the literature will be full of educational values and character. In addition, the literature is also a creative product.Keywords : creativity, literacy, literary texts